Lessons from plants - Montgomery, Beronda L. (Harvard University Press, 2021)
"What would a plant do? It is an unusual question. But, as Beronda L. Montgomery shows, humans can learn a great deal from these organisms. Lessons from Plants unpacks the "senses" and skills of highly adaptive organisms that overcome immense challenges en route to flourishing"--